2016
DOI: 10.1177/1558944716681949
|View full text |Cite
|
Sign up to set email alerts
|

Ten-Year Minimum Follow-Up of 4-Corner Fusion for SLAC and SNAC Wrist

Abstract: Scaphoid excision and 4CF remains a reliable procedure for patients with advanced wrist arthritis. Functional results were good at long-term follow-up despite radiographic changes in the radiolunate joint in 73% of patients. Patient satisfaction was high, and functional impairment was low.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
19
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 25 publications
(30 reference statements)
2
19
0
2
Order By: Relevance
“…1,6,7,12 El gold standard para la artrodesis de 4 esquinas es la cirugía abierta, en donde la configuración de tornillos para la fijación de los huesos del carpo más usada es la bicolumnar, con un tornillo entre semilunar-capitato y otro tornillo entre triquetral-hamato. 4,8,9 Durante los últimos años, esa técnica quirúrgica se ha estado realizando en forma percutánea con asistencia artroscópica con buenos resultados en algunas publicaciones, 6,7 en donde los autores describen algunas ventajas por sobre la técnica abierta dadas por el menor daño a tejidos, al ser una técnica mínimamente invasiva, mayor protección del aporte sanguíneo, preservación de la propiocepción y mejores resultados estáticos. 6,7 En el presente trabajo se muestra la técnica quirúrgica realizada mediante cirugía abierta y la realizada en forma mínimamente invasiva con asistencia artroscópica con buenos resultados para ambas técnicas.…”
Section: Discussionunclassified
“…1,6,7,12 El gold standard para la artrodesis de 4 esquinas es la cirugía abierta, en donde la configuración de tornillos para la fijación de los huesos del carpo más usada es la bicolumnar, con un tornillo entre semilunar-capitato y otro tornillo entre triquetral-hamato. 4,8,9 Durante los últimos años, esa técnica quirúrgica se ha estado realizando en forma percutánea con asistencia artroscópica con buenos resultados en algunas publicaciones, 6,7 en donde los autores describen algunas ventajas por sobre la técnica abierta dadas por el menor daño a tejidos, al ser una técnica mínimamente invasiva, mayor protección del aporte sanguíneo, preservación de la propiocepción y mejores resultados estáticos. 6,7 En el presente trabajo se muestra la técnica quirúrgica realizada mediante cirugía abierta y la realizada en forma mínimamente invasiva con asistencia artroscópica con buenos resultados para ambas técnicas.…”
Section: Discussionunclassified
“…At an average follow-up of 18 years, Traverso et al. described high rates of functional wrists according to the DASH score and with about 50% of normal wrist flexion–extension (Traverso et al., 2017). Likewise, Neubrech et al.…”
Section: Discussionmentioning
confidence: 99%
“…Two systematic reviews of PRC and FCA outcomes did not identify any differences in patient-reported disability, subjective ratings of satisfaction, rate of conversion to total wrist arthrodesis, or increase in grip strength 7 , 8 . Despite these findings and reports that both PRC and FCA can be associated with the development of radiographic evidence of arthrosis at long-term follow-up 6 , 23 , some authors have stated that FCA may provide a more desirable result 6 , 24 - 27 . It is clear that controversy exists with regard to which surgery yields a superior clinical result.…”
mentioning
confidence: 97%
“…For patients with Stage-I or II scapholunate advanced collapse (SLAC) or scaphoid nonunion advanced collapse (SNAC) arthritis for whom motion-sparing surgery is indicated, the optimal treatment remains unclear 3 and has traditionally included either proximal row carpectomy (PRC) or four-corner arthrodesis (FCA) 4 , 5 . Because SLAC arthritis is the most common form of wrist degenerative arthritis 6 , defining the optimal surgical treatment would be an important step in improving patient outcomes while minimizing costs.…”
mentioning
confidence: 99%
See 1 more Smart Citation